On three ectoparasitic monogeneaiis m freshwater fishes of Meerut - Singh, H S; Agarwal, Shilpi; Kumar, Kapil; ., Vibha (Indian Journal of Fisheries, 2011)
The present note deals with three species of freshwater monogeneans. Ancylodiscoides meerutensis n. sp., is characterised by having different shape of cirrus, dorsal anchor and ventral transverse bar. Mizelleus kherai Pandey and Mehta, 1986 has been redescribed as the original account lacks some morphological details including head organ pattern, seminal vesicle etc. sSilurodiscoides elongatus n. sp., is characterised in having an accessory piece on dorsal anchors, presence of wings on dorsal anchons presence of cephalic glands, difference in shape of copulatory complex and vagina and in number of head organs.